The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40670-015-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Multidisciplinary First Year Students to Learn Anatomy Via Stimulating Teaching and Active, Experiential Learning Approaches

Abstract: Student engagement requires both a stimulating teaching style and provision of meaningfully learning activities involving student peer interactions. This study compares student engagement levels between two different styles and strategies for teaching first year anatomy: a stimulating (passionate) teaching style with active, self-directed experiential learning strategies versus a more traditional didactic teaching style and strategies. In 2008-2011, first-year JCU medicine and health science students undertaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 21 publications
7
46
2
Order By: Relevance
“…"Activists" are those who prefer to learn by activity such as brainstorming or problem solving, who benefit most in relation to learning from group discussions or role play exercises, and are keen to explore new learning experiences. The present data do, however, appear to conflict with recent results, which have shown that students who employ more active, self-directed experiential learning strategies report greater interest and engagement in anatomy learning activities, as well as demonstrating increased interaction with peers and instructors (Diaz and Woolley, 2015). The present data do, however, appear to conflict with recent results, which have shown that students who employ more active, self-directed experiential learning strategies report greater interest and engagement in anatomy learning activities, as well as demonstrating increased interaction with peers and instructors (Diaz and Woolley, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…"Activists" are those who prefer to learn by activity such as brainstorming or problem solving, who benefit most in relation to learning from group discussions or role play exercises, and are keen to explore new learning experiences. The present data do, however, appear to conflict with recent results, which have shown that students who employ more active, self-directed experiential learning strategies report greater interest and engagement in anatomy learning activities, as well as demonstrating increased interaction with peers and instructors (Diaz and Woolley, 2015). The present data do, however, appear to conflict with recent results, which have shown that students who employ more active, self-directed experiential learning strategies report greater interest and engagement in anatomy learning activities, as well as demonstrating increased interaction with peers and instructors (Diaz and Woolley, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…However, it has been demonstrated that they also have a tendency towards poor time management skills, and may not be as adept at careful planning of academic activities (Lashley and Barron, ). The present data do, however, appear to conflict with recent results, which have shown that students who employ more active, self‐directed experiential learning strategies report greater interest and engagement in anatomy learning activities, as well as demonstrating increased interaction with peers and instructors (Diaz and Woolley, ). It may be that the tendency to employ such strategies is not captured within the LSQ “Activist” learning style classification.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to perceiving an increased understanding of gross anatomy and histology, participants in the experimental group reported MR to be an interactive and engaging way to learn anatomy. This finding supports the idea that favorable perceptions of a learning activity can produce better learning outcomes [5].…”
Section: Discussionsupporting
confidence: 82%
“…Professor Diaz in a survey found that 83% of health sciences students thought that practical, innovative approaches assisted their deeper understanding of Anatomy, 81% thought they assisted their long-term memory of anatomy, and 82% reported that the learning and memory skills they acquired in anatomy have been useful in other subjects. 17 Students have transferred this review strategy to other classes and the peer teachers developed and expressed an interest in it as an adjunct teaching tool.…”
Section: Discussionmentioning
confidence: 99%